Proteomic analysis of metronidazole resistance in the human facultative pathogen Bacteroides fragilis - Paunkov, Ana; Hummel, Karin; Strasser, Doris; Sóki, József; Leitsch, David (Frontiers in Microbiology, 2023)
The anaerobic gut bacteria and opportunistic pathogen Bacteroides fragilis can cause life-threatening infections when leaving its niche and reaching body sites outside of the gut. The antimicrobial metronidazole is a mainstay in the treatment of anaerobic infections and also highly effective against Bacteroides spp. Although resistance rates have remained low in general, metronidazole resistance does occur in B. fragilis and can favor fatal disease outcomes. Most metronidazole-resistant Bacteroides isolates harbor nim genes, commonly believed to encode for nitroreductases which deactivate metronidazole. Recent research, however, suggest that the mode of resistance mediated by Nim proteins might be more complex than anticipated because they affect the cellular metabolism, e.g. by increasing the activity of pyruvate:ferredoxin oxidoreductase (PFOR). Moreover, although nim genes confer only low-level metronidazole resistance to Bacteroides, high-level resistance can be much easier induced in the laboratory in the presence of a nim gene than without. Due to these observations we hypothesized that nim genes might induce changes in the B. fragilis proteome and performed comparative mass-spectrometric analyses with B. fragilis 638R, either with or without the nimA gene. Further, we compared protein expression profiles in both strains after induction of high-level metronidazole resistance. Interestingly, only few proteins were repeatedly found to be differentially expressed in strain 638R with the nimA gene, one of them being the flavodiiron protein FprA, an enzyme involved in oxygen scavenging. After induction of metronidazole resistance, a far higher number of proteins were found to be differentially expressed in 638R without nimA than in 638R with nimA. In the former, factors for the import of hemin were strongly downregulated, indicating impaired iron import, whereas in the latter the observed changes were not only less numerous but also less specific. Both resistant strains, however, displayed a reduced capability of scavenging oxygen. Susceptibility to metronidazole could be widely restored in resistant 638R without nimA by supplementing growth media with ferrous iron sulfate, but not so in resistant 638R with the nimA gene. Finally, based on the results of this study we present a novel hypothetic model of metronidazole resistance and NimA function.